Evaluasi Kesesuaian Penggunaan Lahan Kota Salatifa Tahun 2010-2014 Terhadap Rencana Tata Ruang Wilayah Kota Salatiga Tahun 2010-2030 - Tusianto, Aditya; , Ir. Taryono, M.Si; , Agus Anggoro Sigit, S.Si., M.Sc (2015)
Salatiga chosen as a study area in this research because of it's strategic position and it's possibility to cause significant changes in land use. Therefore, this study aimed to determine land use changes in Salatiga at 2010-2014 and land use conformity at 2014 with the Salatiga Spatial City Planning 2010-2030. This study was conducted using field checks (survey) which used to match the results of digitized maps of land use in 2014 with the actual conditions, and secondary data analysis done by spatial analysis of overlaying maps (overlay) using the Geographic Information System. Overlay spatial analysis used to determine changes in land use that occurred at 2010-2014 in Salatiga and determine the land use confirmity in 2014 with the Salatiga Spatial City Planning 2010-2030. The results showed that until 2014 there was a land use changes in Salatiga amounted to 142.20 hectares which include the increasing of settlement in amount of 119.12 hectares, industrial in amount of 14.55 hectares, trade amounted to 4.48 hectares and Parks of 1.98 hectares. Land use that categorized in accordance with the Salatiga Spatial City Planning 2010-2030 amounted to 3500.09 hectares or 61.65% from the total area of Salatiga. The type of land use with a high degree of conformity are Landfill, Military, Office, Health Facilities and Worship Facilities. Land use that classified as not appropiate amounted to 1754.27 hectares or 30.90%, and there are 423.15 hectares or 7.45% of land use that is not in accordance with the directives of Salatiga Spatial City Planing 2010-2030.